1984
DOI: 10.1007/bf02534609
|View full text |Cite
|
Sign up to set email alerts
|

High field13C nuclear magnetic resonance spectrum of the olefinic carbons of the triglycerides of palm oil

Abstract: In the triglycerides of palm oil (or any vegetable oil or fat), an unsaturated fatty acid (oleic or linoleic) attached to the 2‐glycerol carbon can be distinguished from one attached to the 1‐ or 3‐glycerol carbon by high (or medium) field13C nuclear magnetic resonance (NMR) analysis of the olefinic carbons. The chemical shift difference of the olefinic carbons in the fatty acid chain is characteristic of the chain's glycerol position and can therefore be used to identify the glycerol position of an unsaturate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

1985
1985
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 6 publications
0
21
0
2
Order By: Relevance
“…The report indicated that, except for the lack of differentiation of the saturated fatty acids, the 13 C NMR technique provided the same information as the tedious enzymatic hydrolysis cum fatty acid analysis (88). The chemical shift difference of the olefinic carbon atoms in the fatty acid chain of triacylglycerols in palm oil was found to be characteristic of the chain's glycerol position and can therefore be used to identify the glycerol position of an unsaturated fatty acid in the triacylglycerol molecule (89).…”
Section: 89mentioning
confidence: 99%
“…The report indicated that, except for the lack of differentiation of the saturated fatty acids, the 13 C NMR technique provided the same information as the tedious enzymatic hydrolysis cum fatty acid analysis (88). The chemical shift difference of the olefinic carbon atoms in the fatty acid chain of triacylglycerols in palm oil was found to be characteristic of the chain's glycerol position and can therefore be used to identify the glycerol position of an unsaturated fatty acid in the triacylglycerol molecule (89).…”
Section: 89mentioning
confidence: 99%
“…A high (or medium) field 13 C NMR spectrum can distinguish the olefinic carbons of the β-chain from those of the -chain [3]. The assignment of the signals to the olefinic carbons of the fatty acid chain attached to the α or β glyceridic positions presented in Figure 1 were done as described by Ng [3].…”
Section: Acyl Positional Distributionmentioning
confidence: 99%
“…The assignment of the signals to the olefinic carbons of the fatty acid chain attached to the α or β glyceridic positions presented in Figure 1 were done as described by Ng [3]. Integration of the pair of peaks for C-9 of the oleic chain and of the pair of peaks for C-10 of the linoleic chain in a spectrum obtained under suitable condition of gated decoupling, permits quantitative analysis of the unsaturated chain attached to the and β positions Tulloch [18].…”
Section: Acyl Positional Distributionmentioning
confidence: 99%
See 2 more Smart Citations